Corn cob innovation into janggel mushroom media and solid organic fertilizer in Gembongan Village - Juwita, Ratna; Manggara, Algafari Bakti; Suharti, Suharti; Aprilia, Ajeng Rachma; Al Farobi, Robbach Najih; Sari, Dian Layung; Aini, Nuril Iftakhul; Anto, Agus (Community Empowerment, 2025)
Gembongan Village, located in Ponggok Sub-district, Blitar Regency, East Java Province, possesses significant potential in the agricultural sector, particularly in corn cultivation. Known for its abundant corn production, the local community is often seen drying corn in front of their houses. However, during the harvest season, the increase in yields gives rise to environmental issues due to the accumulation of unused corn cobs, with only a small portion being repurposed as fuel. This significant volume of agricultural waste necessitates proper management. One proposed solution is to utilize corn cobs as a growing medium for janggel mushrooms (a local variety of mushroom) to support the green economy, as well as a raw material for making organic fertilizer to produce high-quality products using the fermentation method. This community service aims to provide innovative solutions to the corn cob waste problem while building sustainable partnerships with Gembongan Village in line with SDGs 3 and 17. The community service methods applied include field observation for identifying potential and problems, socialization regarding agricultural waste management, hands-on training for making mushroom growing media and organic fertilizer, and continuous mentoring in the form of monitoring and evaluation. The results show that after the training, there was a significant increase in all aspects, with 100% of the participants knowing how to make the mushroom growing media and 92% knowing how to make solid organic fertilizer.